Evaluation of the mixed mode (I/II) fracture toughness of cement emulsified asphalt mortar (CRTS-II) using mixture design of experiments. (20th November 2019) - Najjar, Shima; Mohammadzadeh Moghaddam, Abolfazl; Sahaf, Ali; Rasaei Yazdani, Mohammadreza; Delarami, Aref
Highlights: Low temperature fracture behaviors of cement emulsified mortar were investigated. Fracture behaviors for tensile, shear and mixed tensile-shear were measured. D-Optimal Mixture Design Method was employed. Regression models based on the experimental results were developed. Dependence of fracture mode I, II, and I/II on mix design ratios was demonstrated. Tensile-shear and shear modes revealed lowest and highest fracture toughness. Optimum designs for maximizing fracture toughness of all three modes was delimited. Abstract: Cement emulsified asphalt mortar (CEAM) is a key component of ballastless rail track systems which is tasked with damping the train movement energy and transferring loads to the concrete roadbed. This mortar consists of asphalt emulsion, sand, cement, and water and enjoys better toughness and flexibility properties than cement mortar thanks to the combined effect of cement and asphalt emulsion. One of the primary causes of failure in this mortar is cracking at low temperatures. This study investigated the fracture toughness of CEAM (CRTS- II) with different volume percentages of mortar constituents, namely cement, sand, water, and asphalt emulsion, at low temperature in the linear elastic fracture mechanics (LEFM) framework. The critical stress intensity factors of the mortar for pure tensile (mode I), pure shear (mode II), and mixed tensile-shear (mixed mode I/II) fractures with Me values of respectively 1.0, 0, and 0. 67 were obtained. Considering the necessity of examining the effect of mix design ratios and their interactions and the need to limit these ratios to ensure acceptable rheological and mechanical properties, the experiments were designed using the D-Optimal mixture design method at 5% significance level. By assuming a quadratic model between the critical stress intensity factors of each fracture mode and the volume percentages of mortar constituents, a total of 20 randomized mix designs were obtained. For each mix design, the semi-circular bending (SCB) test was performed with at least 3 replications. The regression models based on the experimental results were developed. The findings demonstrated the dependence of mode I, mode II, and mixed mode I/II critical stress intensity factors on the mix design ratios. The lowest and highest fracture toughness estimates were related to the mixed tensile-shear and pure shear modes, respectively. Finally, the mixture design method was used to delimit the optimum mix design region for maximizing the fracture toughness of all three modes.